High‐Mobility Two‐Dimensional Electron Gas at InGaN/InN Heterointerface Grown by Molecular Beam Epitaxy. Issue 9 (27th June 2018) - Wang, Tao; Wang, Xinqiang; Chen, Zhaoying; Sun, Xiaoxiao; Wang, Ping; Zheng, Xiantong; Rong, Xin; Yang, Liuyun; Guo, Weiwei; Wang, Ding; Cheng, Jianpeng; Lin, Xi; et al.
Abstract: Due to the intrinsic spontaneous and piezoelectric polarization effect, III‐nitride semiconductor heterostructures are promising candidates for generating 2D electron gas (2DEG) system. Among III‐nitrides, InN is predicted to be the best conductive‐channel material because its electrons have the smallest effective mass and it exhibits large band offsets at the heterointerface of GaN/InN or AlN/InN. Until now, that prediction has remained theoretical, due to a giant gap between the optimal growth windows of InN and GaN, and the difficult epitaxial growth of InN in general. The experimental realization of 2DEG at an InGaN/InN heterointerface grown by molecular beam epitaxy is reported here. The directly probed electron mobility and the sheet electron density of the InGaN/InN heterostructure are determined by Hall‐effect measurements at room temperature to be 2.29 × 10 3 cm 2 V −1 s −1 and 2.14 × 10 13 cm −2, respectively, including contribution from the InN bottom layer. The Shubnikov–de Haas results at 3 K confirm that the 2DEG has an electron density of 3.30 × 10 12 cm −2 and a quantum mobility of 1.48 × 10 3 cm 2 V −1 s −1 . The experimental observations of 2DEG at the InGaN/InN heterointerface have paved the way for fabricating higher‐speed transistors based on an InN channel. Abstract : A two‐dimensional electron gas (2DEG) at InGaN/InN heterointerface is demonstrated. The directly probed electron mobility of the heterostructure is 2.29 × 10 3 cm 2 V −1 s −1 at 300 K, while the analysis of Shubnikov‐de Haas (SdH) oscillations at 3 K confirm that the quantum mobility and electron density of the 2DEG are 1.48 × 10 3 cm 2 V −1 s −1 and 3.30 × 10 12 cm −2, respectively.